Perceptions of Family-Level Social Factors That Influence Health Behaviors in Latinx Adolescents and Young Adults at High Risk for Type 2 Diabetes - Erica G. Soltero; Neeku Navabi; Felipe G. Castro; Stephanie L. Ayers; Jenny Mendez; Deborah I. Thompson; Gabriel Q. Shaibi (MDPI AG, 2021)
Given that health behaviors occur within the context of familial social relationships, a deeper understanding of social factors that influence health behaviors in Latinx families is needed to develop more effective diabetes prevention programming. This qualitative study identified perceived family-level social factors that influence health behaviors in Latinx adolescents (12-16 years; N = 16) and young adults (18-24 years; N = 15) with obesity and explored differences in perceptions across sex and age. Participants completed an in-depth interview that was recorded, transcribed, and coded using thematic content analysis. Emergent themes central to health behaviors included: perceived parental roles and responsibilities, perceived family social support for health behaviors, and familial social relationships. Mom's role as primary caregiver and dad's role as a hard worker were seen as barriers to engaging in health behaviors among adolescent females and young adults, males and females. Adolescents perceived receiving more support compared to young adults and males perceived receiving more support compared to females. Health behaviors in both age groups were shaped through early familial social interactions around physical activity. These insights suggest that traditional gender roles, social support, and social interaction around health behaviors are critical components for family-based diabetes prevention programs in high-risk Latinx youth and young adults.